Next generation Direct Wafer® technology delivers low cost, high performance to silicon wafer industry. (September 2017) - van Mierlo, Frank; Jonczyk, Ralf; Qian, Victor
Abstract: Silicon remains the dominant technology worldwide in the PV industry and a tremendous amount of cumulative industry advances have given product based on multicrystalline wafers the lowest LCOE in the market. However, new technologies are emerging that not only promise dramatically lower costs but also demonstrate significant performance gains. In the wafer technology space, novel techniques combined with advanced cell architectures are yielding high-efficiency, low-cost cells. Specifically, kerfless silicon wafers made from molten silicon using Direct Wafer ® technology have the advantage of having a 50% lower production cost and a 66% reduction in energy use and can be produced with new wafer features impossible through conventional wafer manufacturing. These features include: (i) The ability to grow a 3D wafer or a thin wafer with a thick border. The 3D feature further reduces the amount of silicon required for each wafer without sacrificing strength, durability or performance. (ii) The ability to add a doping gradient to the wafer that acts as a built-in back surface field, resulting in at least 0.3% absolute increase in efficiency. Both the addition of a doping gradient and the 3D wafer feature will help to accelerate the silicon PV learning curve and deliver progressively lower costs.